1999
DOI: 10.1023/a:1026660614372
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study aimed to describe the clinical manifestations of celiac sprue related to malnutrition and to analyze the associations between celiac sprue and other diagnoses. A case-control study compared the occurrence of comorbid diagnoses in case and control subjects with and without celiac sprue, respectively. All patients with a primary or secondary diagnosis of celiac sprue (ICD-579.0) who were discharged from hospitals of the Department of Veterans Affairs between 1986 and 1995 were selected as case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The prevalence of CeD (1:100) multiply exceeds that of IBD (CD 0,1–16:10 4 , UC 0,5–25:10 4 ) in general population [ 8 ]. Previous studies showed, that the prevalence of IBD is 5–10 times higher in CeD compared with that of the general population [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CeD (1:100) multiply exceeds that of IBD (CD 0,1–16:10 4 , UC 0,5–25:10 4 ) in general population [ 8 ]. Previous studies showed, that the prevalence of IBD is 5–10 times higher in CeD compared with that of the general population [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider CD[ 25 ] or UC[ 26 ] patients at high risk of presenting CeD[ 27 - 32 ] and others don’t[ 26 , 32 , 33 ]. However, none determine the frequency of HLA-CeD in their patients, although Leeds points out that HLA-CeD could be less frequent in IBD patients than in the general population[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, malnutrition has been ascribed as a cause of chronic pancreatitis in nonalcoholic young patients in underdeveloped countries [42, 43, 44]; this possible etiology has not yet been identified in Mexico [45]. Accordingly, several authors have proposed protein-calorie malnutrition as a mechanism of temporary abnormal pancreatic function in patients with intestinal diseases such as CS [1, 4, 5, 46]. …”
Section: Discussionmentioning
confidence: 99%